Application and multidisciplinary aspects of wireless sensor networks : concepts, integration, and case studies - Gavrilovska, Liljana (New York : Springer, 2011)
This hands-on introduction to WSN systems development covers a broad range of topics in the field, with contributions from researchers involved in the ProSense project. It emphasizes the practical knowledge required for the successful implementation of WSNs
1. Basic issues -- 2. Multidisciplinary issues -- 3. Case studies -- 4. Birds of a feather
Includes bibliographical references and index
Keywords: Sensor networks; Wireless LANs; Wireless sensor networks